2018
DOI: 10.3390/educsci8020040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Community of Inquiry (CoI) within a Massive Open Online Course (MOOC) for In-Service Teachers in Environmental Education

Abstract: Abstract:One of the greatest ways to transform education systems is to develop community-centered professional supports for in-service teachers. Given the rise of distance learning platforms such as massive open online courses (MOOCs), there is a growing potential to deliver such supports at scale. The community of inquiry (CoI) framework models the asynchronous, text-based communication that defines educational experiences within such collaborative learning environments; however, methods of CoI transcript ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
4
28
0
2
Order By: Relevance
“…BMOST partners also perceived many strengths that helped throughout the process and consistently believed that it strengthened their community. As noted in previous research (Kaul et al, ), BMOST presented as a community of inquiry merging leaders through collaborative engagement subsequently building on mutual understanding. The partners believed these initial efforts lead to consistent action or empowerment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…BMOST partners also perceived many strengths that helped throughout the process and consistently believed that it strengthened their community. As noted in previous research (Kaul et al, ), BMOST presented as a community of inquiry merging leaders through collaborative engagement subsequently building on mutual understanding. The partners believed these initial efforts lead to consistent action or empowerment.…”
Section: Discussionmentioning
confidence: 77%
“…Within education, research discussing communities of inquiry (Garrison, Anderson, & Archer, ) indicates that collaborative engagement in discourse and collective reshaping of social constructions is effective at building mutual understanding and action (Kaul, Aksela, & Wu, ). Further, the community of inquiry model requires group cohesion and open communication (Garrison, Anderson, & Archer, ).…”
Section: Literaturementioning
confidence: 99%
“…CE OOE and CE MOOC instructional designs require interdisciplinarity, online and offline networking, co-construction of knowledge between and among educators and learners. This type of co-construction is substantiated among teachers to increase digital literacy of teachers, targeting both pre-service teachers and in-service teachers and sharing educational experiences of in-service teachers in Oyo et al (2017) or with community-centered professional support for in-service teachers in Kaul et al (2018) (Table 2). We argue that through co-construction of innovations (e.g., via interacting OER, MOOCs, VLEs), of processes (e.g., interacting trajectories of teaching and learning) and of outputs (e.g., institutionalized VLEs, development of digital abilities and skills in addition to the learning (Carrera and Ramírez-Hernández 2018)), co-construction of sustainable, circular products, processes, organizations, and even a prospective economy, only then become truly targeted and possible with a contribution from CE OOE substantiated by several various CE MOOC instructional designs.…”
Section: Emerging Educational Tools and Technologies For Ce Ooe And Cmentioning
confidence: 99%
“…As a solution, previous research suggested including online courses into teachers' professional programs [4]. This was also studied in the specific context of mathematics and science education [5,6], but more research is needed to understand the degree to which these courses are relevant to teachers. Teachers prefer to have digital tools and optionality used in their training [7].…”
Section: Introductionmentioning
confidence: 99%